Development of Mobile App for the design of drip irrigation system - NETAM, PRIYANKA; AGRAWAL, NARENDRA; KHALKHO, D.; VICTOR, V. M.; TRIPATHI, M. P. (Journal of Soil and Water Conservation, 2023)
Drip irrigation systems are the most efficient method of irrigation. Drip irrigation systems are a sophisticated and complex one, in which each component plays a very important role. There are large numbers of consideration, which must be taken into account in the design of drip system of irrigation. The efficiency of drip irrigation systems is a function of appropriate design. Appropriate design of drip irrigation systems helped the farmers to bring more area under irrigation. The efficiency of drip systems typically is reported to be 90% or higher. It means, much less water wasted as compared to other systems of irrigation. Many farmers growing vegetables and fruits in India and abroad preferred drip method of irrigation. In order to design economical system of drip irrigation, an Android Mobile App has been developed in the Department of Soil and Water Engineering, Faculty of Agricultural Engineering, IGKV, Raipur with the objective to facilitate the students, officials of Department of Agriculture/Horticulture Government of Chhattisgarh, NGOs and farmers for easily designing the drip irrigation system. Android App was developed to design drip irrigation system for locations specific for different horticultural crops. This computer program was named “Drip Irrigation App” developed using Android Studio Software. The method of complete enumeration was used to find the optimum sizes and numbers of main line, sub-main lateral pipelines, drippers along with water requirement of different crops and pump size. The App requires only few input data and it can calculate large number of data output for the design of drip system for small as well as large area of land. The developed App was tested and found to be satisfactorily.